'(m6)A' stands for 'autoimmunity': reading, writing, and erasing RNA modifications during inflammation. Issue 12 (December 2021) - Bechara, Rami; Gaffen, Sarah L.
Abstract : Covalent RNA modifications that regulate gene expression post transcriptionally, in particular N6 -methyladenosine (m 6 A), are emerging as important regulators of autoimmune responses. Here, we highlight new findings describing the functional diversity and specificity of m 6 A modifications and their regulation in the context of autoimmunity.